Pengaruh Ulasan Produk Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Pada Marketplace Shopee - Kusuma, Aulia Amanah; Murniyati (CV Warnak Johanna Nusantara, 2025)
In an increasingly fierce marketplace competition, purchase decisions are influenced by product reviews and consumer trust. This study aims to analyze the influence of product reviews and consumer trust on purchase decisions on the Shopee marketplace. With a quantitative approach sourced from data from 50 respondents, shopee users are active and have shopped by looking at product reviews and testing with multiple linear regression. The results showed that product reviews had no significant effect on the purchase decision with a t-count score (0.459 < 2.012) and a significance value of 0.000 < 0.05, so that HO1 was accepted, Ha1 was rejected. while consumer confidence had a significant effect on purchase decisions with a t-count score (6.795 > 2.012) and a significance value of 0.000 < 0.05, thus, HO2 was rejected, Ha2 was accepted. In addition, simultaneously product reviews and consumer trust affect purchase decisions on Shopee with a value of f calculated (25,737 > 3.20). This finding states that the importance of consumer trust in a decision-making, Shopee also needs to increase consumer trust through original and informative reviews, as well as highlighting quality reviews with photos or videos.